Detection of Escherichia coli O157 by peptide nucleic acid fluorescence in situ hybridization (PNA-FISH) and comparison to a standard culture method - C. Almeida (2013)
Despite the emergence of non-O157 Shiga toxin-producing Escherichia coli (STEC) infections, E. coli serotype O157 is still the most commonly identified STEC in the world. It causes high morbidity and mortality and has been responsible for a number of outbreaks in many parts of the world. Various methods have been developed to detect this particular serotype, but standard bacteriological methods remain the gold standard. Here, we propose a new peptide nucleic acid fluorescence in situ hybridization (PNA-FISH) method for the rapid detection of E. coli O157. Testing on 54 representative strains showed that the PNA probe is highly sensitive and specific to E. coli O157. The method then was optimized for detection in food samples. Ground beef and unpasteurized milk samples were artificially contaminated with E. coli O157 concentrations ranging from 1 x 10(-2) to 1 x 10(2) CFU per 25 g or ml of food. Samples were then preenriched and analyzed by both the traditional bacteriological method (ISO 16654: 2001) and PNA-FISH. The PNA-FISH method performed well in both types of food matrices with a detection limit of 1 CFU/25 g or ml of food samples. Tests on 60 food samples have shown a specificity value of 100% (95% confidence interval [CI], 82.83 to 100), a sensitivity of 97.22% (95% CI, 83.79 to 99.85%), and an accuracy of 98.33% (CI 95%, 83.41 to 99.91%). Results indicate that PNA-FISH performed as well as the traditional culture methods and can reduce the diagnosis time to 1 day.